CGIAR research priorities for environmental health and biodiversity to advance the three Rio conventions - Masso, C.; Jat, M.L; Stevenson, P.; Mbarak, H.; Alekseeva, N.; Kumar, S.; Ortiz, O.; Milach, S (2025)
The CGIAR 2022-2024 R&I portfolio initiatives were designed with environmental health and biodiversity lenses. Significant lessons have been learnt during the implementation of the initiatives and importantly through engagement in the respective processes of the three Rio Conventions [i.e., Convention on Biological Diversity (CBD), the United Nations Framework Convention on Climate Change (UNFCCC) and the United Nations Conventions to Combat Desertification (UNCCD)]. The CGIAR 2025-2030 R&I portfolio science programs (SP) and accelerators (AC) have been designed to integrate such lessons, with the multifunctional landscapes (MFL) and Sustainable Farming (SF) SP playing a pivotal role.